Terek and Dagestan at the turn of 1917-1918. in the description of general A.I. Denikin - Vladimir B. Lobanov (Кавказология)
The article touches upon the topics related to the reflection of the development of the revolution and the Civil War in the Tersk-Dagestan region at the turn of 1917-1918 in the description of General A.I. Denikin in the 2nd volume of “Essays of the Russian Troubles”. The author examines a wide range of issues related to the revolutionary process in the North Caucasus after the Bolsheviks seized power. The emphasis is on the fact that, due to historical, territorial, and national qualities, one of the first anti-Bolshevik hubs was established in the former Russian Empire’s south-east. Because of historical peculiarities of the region’s development in the period 1917-1920, relations between the Terek Cossacks and nonresidents, and the Terek Cossacks and Ossetians, Chechens and Ingush intensified. To understand the regional alignment of forces, General A.I. Denikin gave brief characteristics of local peoples and their role in revolutionary events. On the one hand, the emphasis is placed on the indomitable, superficial Bolshevism of the mountain peoples who used the revolutionary restructuring of Russian society for self-serving interests, on the other hand, the passive role of the Terek Cossacks was noted, on which, including General A.I. Denikin, hopes were pinned in the fight against regional Bolshevism. Separately, General A.I. Denikin considered two regional attempts to create an interregional military-political movement against the Bolshevization of the North Caucasus. The first concerned the created in May 1917 Union of the United Highlanders of the North Caucasus and Dagestan, later, in December 1917, joined forces with the Terek Cossack government and formed the Provisional Terek-Dagestan Government headed by the Terek ataman M.A. Karaulov. The second attempt, which concerned the creation of a wider representation of the South-Eastern Union in September 1917, seemed to General A.I. Denikin more promising, however, because of prevailing military and political situation in revolutionary Russia in the autumn of 1917, it failed.